A study on antagonistic activity of selected fungi against fungal pathogen associated with pineapple rot disease / Mohamad Nur Akmal Ramdzan - Ramdzan, Mohamad Nur Akmal (Faculty of Plantation and Agrotechnology, 2018)
Pineapple is one of the important industrial crop in Malaysia and has become a source of food consumed by people in Malaysia and also global. The decreasing production of pineapple due to fungal infection can cause losses economic value especially to the growers. One of the main control methods used by grower to control the disease is by application of chemical. However heavy usage of chemical had lead to many problems and contains such as formation of disease resistance and environmental pollution. Therefore, The objectives of this study is to determine the potential of selected fungus as antimicrobial pathogens towards fungal pathogen associated with pineapple rot diseases using dual culture method. Two species of fungus were identified as a pathogen of pineapple rot which are Fusarium, and Colletotrichum. Meanwhile five spp. of fungus has been selected as potential biocontrol agents towards the pathogen namely Colletotrichum, Fusarium Fujikuroi, Fusarium Oxysporum, Trichoderma, and Lasiodiplodia. The observation indicated that selected fungus of Trichoderma, and Lasiodiplodia has potential to suppress the growth of the pathogen.